Insecticidal activity of Tagetes erecta and Tagetes patula extracts and fractions free and microencapsulated. (October 2022) - Cristina e Santos, Pamela; Granero, Filipe Oliveira; Junior, João Luis Bronzel; Pavarini, Ronaldo; Pavarini, Gláucia Maria Pereira; Chorilli, Marlus; Zambom, Carolina Reis; Silva, Luciana Pereira; Silva, Regildo Márcio Gonçalves da
Abstract: This study aimed to characterize T. erecta and T. patula extracts, develop a technique of encapsulation, evaluate insecticidal activity of extracts, fractions and liposomes containing fractions. Extracts were characterized by HPLC-MS/MS. Liposomes were prepared using Dipalmitoylphosphatidylcholine (DPPC) and were characterized by Dynamic Light Scattering (DLS) measuring average size, polydispersion index and zeta potential. Insecticidal evaluation was performed applying extracts on S. frugiperda, and fractions and liposomes on S. zeamais . Characterization of extracts showed several flavonoids in both extracts and characterization by DLS showed formation of liposomes. In the evaluation of insecticidal activity on S. frugiperda, both extracts presented interference in larval viability. In the evaluation of insecticidal activity on S. zeamais, T. erecta Hex/AcOEt (50:50) fraction at 50 mg mL −1 presented 98.33% mortality at the 60th hour, and T. patula Hex/AcOEt (50:50) fraction at 50 mg mL −1 presented 100% mortality at the 48th hour, being these the greatest activities of each species at the lowest concentration and time. Fraction incorporated into liposomes did not present insecticidal activity ( T. erecta fraction = 6.67%; T. patula fraction = 0.00%), demonstrating encapsulation efficacy. Therefore, evaluated extracts presented insectidical activity on the experimental models. Besides, liposomes containing fractions were formed and they interfered in insecticidal activity. Thus, these results provide information of T. erecta and T. patula extracts and fractions, and suggest a possible application in agricultural crops, as well as the use of liposomes technology to encapsulate bioactive compounds with insecticidal activity, supporting new studies. Highlights: T. erecta and T. patula extracts were analyzed by HPLC-MS. Extracts and fractions from T. erecta and T. patula presented insecticidal activity. Liposomes containing T. erecta and T. patula extracts or fractions were formed.